2004
DOI: 10.1016/j.ehj.2004.01.017
|View full text |Cite
|
Sign up to set email alerts
|

Cellular repopulation of myocardial infarction in patients with sex-mismatched heart transplantation*1

Abstract: Myocardial infarction enhances the invasion of extracardiac progenitor cells and their regeneration of endothelial cells. However, a significant differentiation into cardiomyocytes as a physiological mechanism of postischaemic regeneration does not occur in transplanted patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(45 citation statements)
references
References 19 publications
2
42
0
1
Order By: Relevance
“…A three-dimensional screening by confocal laser scan microscopy will also prevent the misinterpretation of infiltrating cells beneath the cardiomyocytes, which otherwise are scored as positive cardiomyocytes. 20 This study indicated that there tends to be a positive correlation between the number of stem cell-derived cardiomyocytes and the proportions of infiltrating cells. Such a cellular infiltrate, occurring during an inflammatory response, may take with it a certain number of stem cells, which ultimately can differentiate into cardiomyocytes.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…A three-dimensional screening by confocal laser scan microscopy will also prevent the misinterpretation of infiltrating cells beneath the cardiomyocytes, which otherwise are scored as positive cardiomyocytes. 20 This study indicated that there tends to be a positive correlation between the number of stem cell-derived cardiomyocytes and the proportions of infiltrating cells. Such a cellular infiltrate, occurring during an inflammatory response, may take with it a certain number of stem cells, which ultimately can differentiate into cardiomyocytes.…”
Section: Discussionmentioning
confidence: 77%
“…However, the reported number of invading stem cells that, evidently, differentiate into cardiomyocytes varied considerably between the various experimental and human studies. 9,10,[14][15][16][17][18][19][20] This heterogeneity is most likely the result of an overestimation of host-derived cardiomyocytes, due to the presence of large number of infiltrating host-derived inflammatory cells and/or to the application of a variety of different detection techniques.…”
Section: Introductionmentioning
confidence: 99%
“…In sex-mismatched heart transplant and using Y chromosome fluorescence in situ hybridization, studies have shown a cardiac chimerism caused by migration of recipient cells to the grafted heart. 33,34 The field of forensics has relied on STR loci for identification of suspects and human remains. In theory, testing haplotypes could allow one to identify the presence of suspect in a large mixture of DNAs, such as in polysuspect cases.…”
Section: The Human Genome Contains Clusters Of Snps That Can Be Amplimentioning
confidence: 99%
“…In vivo, however, although the degree of differentiation still remains controversial, many reports have shown cardiac differentiation potential from BM-derived cells. This evidence was supported by human sexmismatched heart transplantation, where cardiac chimerism was determined in transplanted patients [23][24][25][26]. The percentage of contribution however, was very low in all these cases (0.02% to 0.07%) which raised questions about the physiological relevance of their contribution.…”
Section: Bone Marrow-derived Scmentioning
confidence: 89%